Urgensi Etika Dalam Literasi Digital Di Era Globalisasi - Tanjung, Annisa Qadri; Suciptaningsih, Oktaviani Adhi; Asikin, Nurul (WASIS : Jurnal Ilmiah Pendidikan, 2024)
The purpose of this studywas to describe the importance of ethics in the context of digital literacy in the current era of globalization. By understanding the importance of ethics in digital literacy, it is hoped that this research can provide insights regarding optimizing the benefits of digital technology based on the principles of digital ethics. This research uses a library research method; the data is collected from source books, research articles, and other sources relevant to the topic discussed. The library research results showed that digital literacy has a very important role in facing complex challenges in the current era of globalization. Ethics in digital literacy acts as a guideline in using technology so that it has positive effects and minimizes negative effects. Awareness of digital responsibility is the foundation for a smarter and more empowered society in this digital era. Digital literacy ethics are very important in several ways, such as preventing the spread of false information, fighting cyberbullying and harassing speech, and respecting user privacy. Challenges in implementing digital literacy ethics include a lack of awareness of digital ethics, inequality in access and mastery of technology, regulatory and law enforcement challenges, and the role of education in overcoming challenges. Therefore, the importance of ethics in digital literacy and the role of education is crucial to overcoming various challenges that arise along with the development of technology and information.